State Capacity and Long‐run Economic Performance. (12th September 2014) - Dincecco, Mark; Katz, Gabriel
Abstract : We present new evidence about the long‐run relationship between state capacity – the fiscal and administrative power of states – and economic performance. Our database is novel and spans 11 European countries and four centuries from the Old Regime to World War I. We argue that national governments undertook two political transformations over this period: fiscal centralisation and limited government. We find a significant direct relationship between fiscal centralisation and economic growth. Furthermore, we find that an increase in the state's capacity to extract greater tax revenues was one mechanism through which both political transformations improved economic performance. Our analysis shows systematic evidence that state capacity is an important determinant of long‐run economic growth.